High Ligation of the Inferior Mesenteric Artery Induces Hypoperfusion of the Sigmoid Colon Stump During Anterior Resection - Higashijima, Jun; Kono, Toru; Shimada, Mitsuo; Sugitani, Ayumu; Kashihara, Hideya; Takasu, Chie; Nishi, Masaaki; Tokunaga, Takuya; Yoshikawa, Kozo (Frontiers in Surgery, 2021)
Background : Anastomotic leakage (AL) after colorectal surgery is associated with insufficient vascular perfusion of the anastomotic ends. This study aimed to evaluate the effect of high versus low ligation of the ileocolic artery (ICA) and inferior mesenteric artery (IMA), respectively, on the vascular perfusion of the bowel stumps during ileocecal resection (ICR) and anterior rectal resection (AR). Methods : We retrospectively evaluated patients who underwent ICR or AR from 2016–2020. After stapled bowel resection, real-time indocyanine green fluorescence angiography was performed to measure the fluorescence time (FT) as a marker of the blood flow in the proximal and distal stumps before anastomosis. Results : Patients underwent robotic high AR (HAR) (n = 8), robotic low AR (LAR) (n = 6), laparoscopic HAR (n = 8), or laparoscopic LAR (n = 19). The sigmoid colon and rectal stumps during AR both had a significantly longer FT than the ascending colon and ileal stumps during ICR. High ICA ligation did not affect the FT of the ileal and ascending colon stumps, but significantly prolonged the FT of the sigmoid colon. The LAR group tended to have a higher AL rate than the ICR group, but not the HAR group. High IMA ligation caused significant hypoperfusion of the sigmoid colon stump during AR compared with low IMA ligation. The AL rate was similar after low versus high ligation. Conclusions : Low vascular perfusion of the bowel stumps is not an absolute risk factor for AL. High IMA ligation induced sigmoid colon stump hypoperfusion during AR.